Ultra high molecular weight polyethylene and its reinforcement with Carbon Nanotubes in Medical Devices - Rui Miranda Guedes (2015)
This chapter discusses the advantages and complexities of ultra high molecular weight polyethylene (UHMWPE) when used as a bearing material for total joint arthroplasty (TJA) and total knee arthroplasty (TKA). The UHMWPE internal structure and its mechanical response depend strongly on a diversity of factors that include radiation crosslinking, fiber reinforcement, and the addition of antioxidants such as Vitamin E or Vitamin C. All these manufacturing procedures induce morphological changes and simultaneously alter the mechanical properties of UHMWPE. The importance of UHMWPE on arthroplasty, including the advantages, the limitations and the strategies devised to overcome the known drawbacks are discussed in the first section. The following sections revise and discuss the biocompatibility, the manufacturing processes, the tribological behaviour, the aging by oxidation and irradiation of UHMWPE and UHMWPE-CNT nanocomposites. The last section analyses the viscoelastic behavior of UHMWPE and its implications on the long-term survival of total joint arthroplasty.